Bimetallic nanocatalysts PtCu and PtNi for fuel cells - Chernikova , O. M.; Ogorodnik, Y. V. (Physics and Chemistry of Solid State, 2020)
We review the physical mechanisms of heterogeneous catalytic oxidizing reactions methanol oxidation using bimetallic film layered mechanically strained PtNi and PtCu-based catalysts. The main research methods are theoretical calculations based on the density functional theory and the ˝ab initio˝ pseudopotential method. The work illustrates that the mechanical stress and the presence of dissociated oxygen have the greatest impact on increasing electron bimetallic catalyst activity during the oxidation of methanol with using bimetallic layered mechanically strained PtNi and PtCu-based catalysts. The compression of the platinum film pushes the electron density outside the film and it gives the density an elongated form and increases the chemical and absorption activity of the film.